Efektivitas Model Pembelajaran Tutor Sebaya Dalam Meningkatkan Prestasi Belajar - Rahmawati, Aslihatul; Halimah, Nur; Azhari, Ainul (Eduka : Jurnal Pendidikan, Hukum, dan Bisnis, 2024)
This research was conducted with the aim of finding out differences in student learning achievement before and after implementing the peer tutoring model. The total population was 99 students, using saturated sampling techniques. This research used a pre-experimental research design with a one group pretest-posttest design, using the Paired Wilcoxon Test to obtain Sig. 0.000<0.05 means that the student's learning achievement after being treated is different from the score before the student was treated with the peer tutoring model. Keywords: Peer Tutors, Learning Achievement